Inequalities in infant mortality in Italy - Silvia Simeoni; Luisa Frova; Mario De Curtis (BMC, 2019)
Abstract Background All the children of the world should be born equal, but this is not so: even in Italy, there are striking differences already at birth. Neonatal and infant mortality are accurate indexes to assess the demographic wellbeing and quality of life of a population. The aim of the present study is to analyze the infant (IMR) and neonatal (NMR) mortality rates of Italian and foreign children and to evaluate if there is a disparity among geographical macro-areas. Methods Data from 2006 to 2015 were collected by the Italian Statistics Bureau (ISTAT) and extracted from two different national databases, which considered i) underlying cause of death and ii) birth registry. Mortality rates were calculated using conventional definitions. The main analyses were made comparing Italian versus foreigners as a single category as well as by country origin and contrasting Northern residents versus Southern ones. Comparisons between groups were done using relative risks. Results Data show disparity in neonatal and infant mortality among immigrant and Italian residents. In 2015, neonatal (3.0 vs. 1.8/1000) and infant (4.5 vs 2.6/1000) mortality rates were higher among foreign children compared to Italian children. Among babies born to immigrant women, there is a higher infant mortality among children born to women coming from Central and South Africa (8.2 /1000). Inequalities are reported even among Italian regions: in Southern Italy, infant mortality is 1.4 fold higher than in Northern Italy. Conclusion Inequalities in neonatal and infant mortality are evident between Italians and immigrants and among geographical macro-areas There is therefore urgent need for a political and social plan focusing on infancy.